The Application of One-Hour Static Qigong Program to Decrease Needle Pain of Korean Adolescents With Type 1 Diabetes: A Randomized Crossover Design - Euiyeon Kim PhD; Ji-Eun Lee MD, PhD; Min Sohn RN, PhD (SAGE Publishing, 2017)
The aim of this study was to describe application of a static Qigong program to decrease needle pain in Korean adolescents with type 1 diabetes and its pilot test results. The pilot study was a randomized crossover design including 26 adolescents randomized to Qigong or rest group. Participants received a 60-minute Qigong program consisted of warm up, deep breathing, imaginary, and a closing warm up. After 24-hour washout period, treatment assignments were switched. We collected before and after intervention using a self-administered questionnaire, which included the faces pain scale to assess expected and perceived pain during blood sugar testing and insulin injection and the Positive and Negative Affect Schedule. Only expected pain on insulin injection was significantly lower after intervention ( P = .025). The results suggested that the devised static Qigong program was feasible intervention to decrease at least expected pain on insulin injection of adolescents with type 1 diabetes.